How Are We Doing After 30 Years? A Meta-Analytic Review of the Antecedents and Outcomes of Feedback-Seeking Behavior - Anseel, Frederik; Beatty, Adam S.; Shen, Winny; Lievens, Filip; Sackett, Paul R. (Journal of Management, 2015)
This study provides meta-analytic estimates of the antecedents and consequences of feedback-seeking behavior (FSB). Clear support was found for the guiding cost/benefit framework in the feedback-seeking domain. Organizational tenure, job tenure, and age were negatively related to FSB. Learning and performance goal orientation, external feedback propensity, frequent positive feedback, high self-esteem, a transformational leadership style, and a high-quality relationship were positively associated with FSB. Challenging some of the dominant views in the feedback-seeking domain, the relationship between uncertainty and FSB was negative and the relationship between FSB and performance was small. Finally, inquiry and monitoring are not interchangeable feedback-seeking tactics. So FSB is best represented as an aggregate model instead of a latent model. In the discussion, gaps in the current FSB knowledge are identified and a research agenda for the future is put forward. Future research may benefit from (a) a systematic and integrative effort examining antecedents of both feedback-seeking strategies on the basis of a self-motives framework, (b) adopting a process perspective of feedback-seeking interactions, and (c) taking the iterative nature of feedback into account.